The Effects of Minimum Wage, SMEs, and Investment on Employment Absorption - Hikmah, Lila Silviatul; Sishadiyati, Sishadiyati (PT. EQUATOR SINAR AKADEMIA, 2024)
The central issue faced by Indonesia is how to optimize its abundant yet undertrained human resources to support development. The goal is for the majority of the population not to be a burden on development but rather to be an asset in advancing the country. In the context of economic development in developing countries, such efforts aim to increase economic growth, provide more job opportunities, absorb abundant labor, equalize income distribution, reduce regional disparities, and achieve a balanced economic structure. This research will discuss several ideas regarding the role of Provincial Minimum Wage, the number of Micro, Small, and Medium Enterprises (MSMEs), and the value of MSME investments in the aspect of labor absorption in East Java Province. This research activity is conducted to understand whether the Provincial Minimum Wage, the number of MSMEs, and the value of MSME investments contribute to labor absorption and to compare the analysis results of these sectors regarding labor absorption. This research is important because Micro, Small, and Medium Enterprises (MSMEs) are not only economic drivers but also major determinants of employment. In-depth understanding of this sector's role in the economic growth of East Java Province will provide a solid foundation for development planning in terms of sustainable labor absorption. This research applies a quantitative approach and uses secondary data from the years 2013-2022. The method used is multiple linear regression analysis using the SPSS application.